Prebiotic Supplementation During Gestation Induces a Tolerogenic Environment and a Protective Microbiota in Offspring Mitigating Food Allergy - Selle, Amandine; Brosseau, Carole; Dijk, Wieneke; Duval, Angéline; Bouchaud, Grégory; Rousseaux, Anais; Bruneau, Aurélia; Cherbuy, Claire; Mariadassou, Mahendra; Cariou, Véronique; Barbarot, Sebastien; Bodinier, Marie (Frontiers in Immunology, 2022)
Food allergy is associated with alterations in the gut microbiota, epithelial barrier, and immune tolerance. These dysfunctions are observed within the first months of life, indicating that early intervention is crucial for disease prevention. Preventive nutritional strategies with prebiotics are an attractive option, as prebiotics such as galacto-oligosaccharides and inulin can promote tolerance, epithelial barrier reinforcement, and gut microbiota modulation. Nonetheless, the ideal period for intervention remains unknown. Here, we investigated whether galacto-oligosaccharide/inulin supplementation during gestation could protect offspring from wheat allergy development in BALB/cJRj mice. We demonstrated that gestational prebiotic supplementation promoted the presence of beneficial strains in the fecal microbiota of dams during gestation and partially during mid-lactation. This specific microbiota was transferred to their offspring and maintained to adulthood. The presence of B and T regulatory immune cell subsets was also increased in the lymph nodes of offspring born from supplemented mothers, suggestive of a more tolerogenic immune environment. Indeed, antenatal prebiotic supplementation reduced the development of wheat allergy symptoms in offspring. Our study thus demonstrates that prebiotic supplementation during pregnancy induces, in the offspring, a tolerogenic environment and a microbial imprint that mitigates food allergy development.